2015
DOI: 10.1186/s13059-015-0623-3
|View full text |Cite
|
Sign up to set email alerts
|

The genomes of two key bumblebee species with primitive eusocial organization

Abstract: BackgroundThe shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats.ResultsWe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
412
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 352 publications
(436 citation statements)
references
References 214 publications
(281 reference statements)
24
412
0
Order By: Relevance
“…AMPs are classified based on their molecular structure as well as on the presence of particular amino acid residues [1]. The number of different AMPs present in any one organism varies considerably, with more than 50 in some insects [6], six in the honeybee, Apis mellifera [7], with the recently sequenced bumblebees having only four [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…AMPs are classified based on their molecular structure as well as on the presence of particular amino acid residues [1]. The number of different AMPs present in any one organism varies considerably, with more than 50 in some insects [6], six in the honeybee, Apis mellifera [7], with the recently sequenced bumblebees having only four [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, honey bees would not rely on innate immunity as much as solitary insects. However, more recent comparative genomic studies of multiple insect genomes across different levels of social organization, indicated that eusociality by itself does not appear to affect the number of immunity-related genes in hymenopteran ants and bees (Wurm and Keller, 2010;Smith et al, 2011;Simola et al, 2013;Roux et al, 2014;Barribeau et al, 2015;Grozinger and Robinson, 2015;Kapheim et al, 2015;Sadd et al, 2015) or isopteran termites (Terrapon et al, 2014;Korb et al, 2015), challenging the previous hypothesis of eusociality causing relaxed selection on innate immunity. While these further analyses have supplied evidence that eusociality by itself is not associated with the reduction in immune-gene counts, the old claim is still being propagated in the recent literature (e.g., Nish and Medzhitov, 2011;Gadau et al, 2012;Mattila et al, 2012;Schöning et al, 2012;Evison et al, 2013;Meunier, 2015).…”
mentioning
confidence: 67%
“…This is an experiment on the effects of hypoxic conditions on MCF7 cells (Camps et al 2014), organized into a time series of four points, each with two biological replicates, Normoxia (N00), Hypoxia at 16 h (H16), Hypoxia at 32 h (H32), and Hypoxia at 48 h (H48). The additional examples presented in the Supplemental Information are based on publicly available B. terrestris data (GSE64512) consisting of two samples, with four biological replicates each (Sadd et al 2015) and a publicly available A. thaliana data (GSE35562, GSM1178880 to GSM1178882 for the wild-type and GSM1178883 to GSM1178885 for the Hen1-8 mutant) consisting of two samples, with three biological replicates each (Zhai et al 2013).…”
Section: Methodsmentioning
confidence: 99%